Chemical Form of Dietary Selenium Affects the Fatty Acids Profile and Oxidative Stability of Muscles of Broilers Supplemented with Lycopene and Oils. Issue 2 (7th November 2019) - Czauderna, Marian; Białek, Małgorzata; Białek, Agnieszka; Śliwiński, Bogdan; Brzóska, Franciszek
Abstract: The aim of this study is to determine the effects of the addition of different chemical forms of selenium (Se)—selenate (SeVI) or selenized yeast (SeY) to chickens' diet containing equal amounts of fish (FO) and sunflower oils and lycopene (Lyc) on fatty acids (FA) profile and peroxidation yield in thigh muscles of chickens. FA profile is analyzed by gas chromatography coupled with mass spectrometry while content of malondialdehyde is determined by ultra‐fast liquid chromatography (UPLC) with photodiode detection. The diets containing SeY or SeVI increase the feed conversion efficiency of chickens compared with the control diet. SeY or SeVI added to the diet containing Lyc and FO stimulates concentrations of monounsaturated and polyunsaturated (PUFA) FA in muscles. Muscles of chickens fed a diet only with Lyc and FO have the highest indices of atherogenic (A‐SFA) and thrombogenic (T‐SFA) saturated FA and the highest ratios of A‐SFA and T‐SFA to all assayed FA. Dietary Se‐compounds also decrease the PUFA peroxidation indices in muscles compared with the diet containing only FO and Lyc. Therefore Se‐compounds may be added to diets including FO and Lyc to improve the growth parameters, nutritive value, and oxidative stability of chicken meat. Practical Applications : Poultry meat, which is characterized by high protein content of high biological value, high minerals and vitamins, and low collagen and fat content, is recommended as particularly desirable in a balanced diet to replace red and highly processed meat. Also, relatively good price makes this type of meat one of the most popular among consumers. The present study aims to check if inclusion of different chemical forms of selenium into chickens' diets improves nutritional value of broiler meat. Feeding chickens with seleno‐supplements significantly enhances poultry production efficiency and nutritional value of broilers' meat, because it favorably modifies FA composition (enhanced monounsaturated and polyunsaturated FA and decrease atherogenic and thrombogenic saturated FA in muscles) and reduces lipid oxidation in chickens' meat. These results are important from the both producers' and consumers' point of view and correspond to contemporary nutritional recommendations. Abstract : The present study evaluates the influence of the addition of either organic or inorganic forms of selenium into chickens' diet containing lycopene and fish oil on performance parameters, as well as on the chemical composition of broilers' meat. Selenium supplementation enhances poultry production efficiency and favorably modifies fatty acids composition as well as significantly reducing lipid oxidation of thigh muscles.